The Effect of Sport Sponsorship on Brand Equity: A Study Within the Context of Professional Soccer - Hunt, James B.; Hunt, Tammy G. (Archives of Business Research, 2022)
This study examines the effects of sport sponsorship on brand equity. More precisely, the impact of sport sponsorship is assessed for each of Aaker’s (1991) components of brand equity: brand personality; brand awareness; brand associations; perceived quality; brand loyalty. Research is conducted within the domain of a sports team sponsorship, specifically Nivea Men’s sponsorship of Liverpool Football Club. The results demonstrate that all five components of brand equity are positively influenced by sport sponsorship, ultimately supporting the proposition that sport sponsorship has a positive impact on brand equity. While sponsorship may not by itself be sufficient for brand equity building or sales enhancement, sponsors should be able to leverage their association with the team to promote their benefits and motivate fan engagement.